Analysis of Global Climate Change and Adaptation in the Plantation and Forestry Sector in Sesaot Village, Narmada District, West Lombok, West Nusa Tenggara - Jupri, Ahmad; Ahyadi, Hilman; Anggraeni, Marsella; Wahyudi, Alpan; Sagita, Baiq Vira Emaliyana; Aini, Diah Kurotul; Rifwan, Moh. Nurkholis; Yulianti, Yulianti (Jurnal Biologi Tropis, 2024)
The global climate changes that are currently occurring can have a significant impact on the plantation and forestry sectors in Sesaot Village, West Lombok Regency. Even though the plantation technology used by the people of Sesaot Village is still traditional, there are also very diverse types of plantation crops in the village which can make a significant contribution to the local economy, the main challenge faced is increasing temperatures which have the potential to reduce harvest yields and forest productivity. Due to changes in temperature experienced by the community from year to year, it shows a significant increasing trend. Based on data from the West Lombok Regency Meteorology, Climatology and Geophysics Agency (BMKG), the period from 1997 to 2024 in May shows a trend of increasing temperatures that continues from year to year. This research aims to analyze the concrete impact of global climate change and adaptation on the plantation and forestry sectors in Sesaot Village. In facing this challenge, cooperation between government, society and other related parties is very important. Efforts to increase awareness of the impacts of climate change and encourage the adoption of modern technology in the plantation sector can be key steps in mitigating possible negative impacts.